Evaluation of a multidisciplinary, multimodal pain management protocol following pancreas transplantation. Issue 1 (7th December 2022) - Lindner, Brian K.; Lakhani, Shahzia A.; Cooper, Matthew; Nguyen, Brian M.; Vranic, Gayle; Yi, Soo Y.; Abrams, Peter
Abstract: Introduction: Patients undergoing solid‐organ transplantation demonstrate pain arising from both the surgical intervention and pre‐existing comorbidities. High levels of opioid use both pre‐ and post‐transplant are associated with unfavorable transplant outcomes. Patient education, multimodal therapy, and discharge planning have all been demonstrated to reduce opioid use after transplant. Methods: This is a single‐center, retrospective study analyzing patients before and after implementation of a multimodal, multidisciplinary pain management protocol. Morphine milligram equivalents (MMEs) use during the index transplant hospitalization and the need for opioids at discharge was compared between the pre‐ and post‐protocol groups. Results: A total of 52 patients were included in the study, 31 in the pre and 21 in the post‐protocol groups. Inpatient MME use was reduced from 135.5 to 67.5 MMEs after protocol implementation. Additionally, the number of patients discharged on opioids following transplant decreased from 90.3% to 47.6%. Pain scores, length of stay (LOS), and return of bowel function was not different between groups. Conclusion: The implementation of a multimodal, multidisciplinary pain management protocol significantly decreased opioid use during the post‐surgical hospitalization and in the 6 months following transplantation. A combination of non‐opioid analgesics, patient education, and discharge planning can be beneficial elements in pancreas transplant pain management.